Education and ICT in the age of knowledge society - Merlino, Vincenza (IJRDO- Journal of Educational Research, 2019)
This paper presents a critical-speculative discussion on the introduction and steady development of ICT in the social sphere in general, and in the education one in particular, in the frame of the increasing emphasis that is located on what is now used to be defined as "knowledge society", which follows the industrial society model, replacing to the material possessions, as an expression of wealth, the intangible ones, i.e., knowledge, as economic resources. Therefore, starting from the premise that ICT cannot simply be considered as a new "medium" that genuinely changes the communicative relationship among people, and therefore the dissemination and use of knowledge, it is argued about the need for a broader debate on the subject, shifting the focus on an assessment of ICT as a phenomenon part of a deep cultural revolution, with respect to which the process of change involves the education sphere, and regards the role that the education must take in respect of a transformation that involves not only its form but also its nature as the potential for future generations.